2022
DOI: 10.1007/s40273-022-01141-x
|View full text |Cite
|
Sign up to set email alerts
|

Target Trial Emulation for Transparent and Robust Estimation of Treatment Effects for Health Technology Assessment Using Real-World Data: Opportunities and Challenges

Abstract: Key points for decision makers-Deriving treatment effects from real-world data (RWD) can be viewed as an attempt to emulate a randomised experiment, the target trial, that would answer the question of interest. By explicitly describing the target trial and emulating it using RWD, target trial emulation (TTE) can help prevent common pitfalls and biases in non-randomised studies.-We identified several areas where TTE can be used to complement randomised evidence to inform health technology assessment (HTA): 1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Interest in the target trial emulation framework is gaining momentum in human epidemiology [ 76 ], with the current study being one of the pioneering applications of target trial emulation in the veterinary field. The framework aims to make the ‘target trial’ explicit, which helps avoid common design flaws and methodological pitfalls in the analysis of non-randomised studies, keeping each step transparent and accessible [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the target trial emulation framework is gaining momentum in human epidemiology [ 76 ], with the current study being one of the pioneering applications of target trial emulation in the veterinary field. The framework aims to make the ‘target trial’ explicit, which helps avoid common design flaws and methodological pitfalls in the analysis of non-randomised studies, keeping each step transparent and accessible [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every attempt is made to emulate the features of the targeted RCT, except that randomization is not conducted. 57,58 Early emulation studies have shown that discrepancies in effect estimates between RCTs and NRSIs that address a similar question are to a lesser extent the result of unmeasured confounding and can be largely explained by differences in study design and analytic methods, such as time since disease onset and duration of followup. [59][60][61][62] However, unmeasured confounding and other issues are still important and may not be adequately addressed in some trial emulation studies.…”
Section: Advanced Analytic Approaches: Trial Emulation Effortsmentioning
confidence: 99%
“…The framework outlines items to be reported in the protocol of a target trial and its emulation, including: eligibility criteria, treatment strategies, assignment procedures, follow-up period, outcome(s), causal contrast(s), and analysis plan. Since the introduction of the framework, several articles have been published to assist researchers in conducting these studies and educating clinicians and other end users to interpret their findings . However, there is limited understanding of how researchers have implemented the target trial framework when reporting observational analyses with the explicit aim to emulate a target trial.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of the framework, several articles have been published to assist researchers in conducting these studies and educating clinicians and other end users to interpret their findings. 3 , 5 , 11 , 12 , 13 , 14 However, there is limited understanding of how researchers have implemented the target trial framework when reporting observational analyses with the explicit aim to emulate a target trial.…”
Section: Introductionmentioning
confidence: 99%